Lord Hades's ruthless marriage. 1 - Ueji, Yūho (Yen Press, 2023)
'Deep below the earth lies the abode of Lord Hades, the ruthless king of the Underworld. Ruling over the realm of the dead, he swears to never fall in love... Except, well, he kind of just took an arrow to the face courtesy of the primordial god of love, Eros, so... In any case, if someone could please pull this thing out of his head anytime this week, the lord god has placed to be and people to see. He'll even make a wish come true, so step right up! Chop-chop! Who will be the lucky duck to claim Hades's prize...?!"--Back cover.